Estudo experimental comparativo entre as telas de polipropileno, polipropileno+poliglactina e polipropileno+titânio: citocinas pró-inflamatórias, reação inflamatória tecidual e deposição do colágeno - Pereira-Lucena, Cristina Gama [UNIFESP] (2009)
Purpose: Incisional hernia occurs in approximately 11% of all laparotomies. Changes in collagen have been closely implicated in its pathogenesis. The high recurrence rate (45 to 54%) after primary suture has stimulated the development of meshes. Currently, meshes are the biomaterials implant group most used in medicine. This study aims to compare the serum and tissue inflammatory responses and collagen deposition caused by meshes made of polypropylene, polypropylene + polyglactin and polypropylene + titanium. Methods: Thirty Wistar rats were divided into three groups. In group A, a high-density polypropylene mesh was positioned on the abdominal wall. In groups B and C, lowdensity meshes were used in associations with polyglactin and titanium, respectively. Immediately before the operation and on the first, third and fortieth postoperative days, pro-inflammatory cytokines were assayed. On the 40th postoperative day, the region of the inserted prosthesis was biopsied. Hematoxylin-eosin and Masson’s trichrome colorations were used to value the tissue inflammatory reaction with a scale for objective scoring. The scale had six itens: cellular layers in granulomas periphery, inflammatory response in host tissue, inflammatory response in the mesh surface, tissue ingrowth, granulomas and muscular invasion by the inflammatory reaction. For collagen, picrosirius was used with data reading using the Image Tool computer software. Statistics tools: Kruskal Wallis and Dunn tests (HE e Masson) and ANOVA with Bonferroni test (collagen and cytokines). Results: Cytokines: there were no statistically significant differences between the groups. Histology: on the 40th postoperative day in group A, there were fewer inflammatory tissue response and greater collagen deposition (P<0.01). In group B, there were greater inflammatory tissue response and less collagen deposition (P<0.01). Group C presented intermediate values between groups A and B. Conclusions: There were no significant differences in cytokine levels between the groups in the present study. In the animals with the polypropylene + polyglactin mesh implant there was the most intense inflammatory process with lower tissue maturation and collagen deposition on the 40th postoperative day. The polypropylene mesh presented a less severe late inflammatory process, with greater tissue maturation and collagen deposition. The polypropylene + titanium mesh presented intermediate values between the others.